Griefwork online: Perinatal loss, lifecourse disruption and online support. (September 2014) - Davidson, Deborah; Letherby, Gayle
Abstract The Internet provides new opportunities for accessing and giving support following perinatal loss and in this article we report on a project concerned to explore the use of social networking and online networks following such an experience. Perinatal loss can be defined and perceived as biographical disruption yet this type of loss sometimes lacks social recognition. Our ethnographic study reveals that not only do mothers, and sometimes fathers and grandmothers, seek support on the Internet but they also engage in griefwork (the work the bereaved do with others).